Criminology Study on the Circulation of the Sopi Traditional Liquor in the Villages of Zeith, Asilulu, and Kaitetu during the Covid-19 Pandemic - Margie Gladies Sopacua (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
The case of “sopi” traditional drink when consumed in a group gathering and party celebrations tends to cause chaos and commotion that disrupts activities or community harmony, especially in the villages of Zeith, Asilulu and Kaitetu during the covid-19 pandemic. The purpose of this paper was to examine and discuss the factors that cause the circulation of liquor in the villages of Zeith, Asilulu and Kaitetu (Kalauli sub-village) during this pandemic. The research method used was the empirical juridical method with an emphasis on legal theories and rules related to the problems studied and to the existing reality regarding what factors affect the society. This study showed that social control is an effort to prevent the circulation of traditional liquor in the form of sopi in the villages of Zeith, Asilulu and Kaitetu (Kalauli Sub-Village). Liquor is not only circulated among adults but has reached teenagers, and the factors that cause the circulation of this liquor during the covid-19 pandemic are economic, supervisory, and environmental factors. The most important of these three factors is economic factors. The efforts made in the distribution of traditional liquor in the villages of Zeith, Asilulu and Kaitetu during the pandemic are Pre-emptive and Preventive efforts.